Success Plan for the Online Learning Experience: Student Engagement, Teacher Accessibility, & Relationships - Ruchelle Combs (Middle Grades Review, 2020)
Online teaching in the time of COVID-19 is a new and sometimes scary experience for even the most seasoned educator. It is certainly apparent that many students are struggling to make this instantaneous adjustment. Teachers have a duty to mitigate this stress as they continue to provide relevant instruction. Based on my experience, this can be achieved by fostering student engagement, staying highly accessible, and maintaining the relationships that were formed face-to-face in the conventional classroom.
Keywords: COVID-19; engagement; relationships; accessibility; adolescent